2018
DOI: 10.3174/ajnr.a5526
|View full text |Cite
|
Sign up to set email alerts
|

Local Glioma Cells Are Associated with Vascular Dysregulation

Abstract: BACKGROUND AND PURPOSE:Malignant glioma is a highly infiltrative malignancy that causes variable disruptions to the structure and function of the cerebrovasculature. While many of these structural disruptions have known correlative histopathologic alterations, the mechanisms underlying vascular dysfunction identified by resting-state blood oxygen level-dependent imaging are not yet known. The purpose of this study was to characterize the alterations that correlate with a blood oxygen level-dependent biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In regard to resting-state fMRI, our results suggest that both neuronal desynchronization and neurovascular disruption could contribute to apparent changes in fMRI-based measures of “functional connectivity” related to tumor progression ( Dierker et al, 2017 ; Hadjiabadi et al, 2018 ). Nevertheless, these results do suggest a firm physiological basis for studies that have noted the ability of resting state fMRI data to delineate glioma tumor boundaries ( Agarwal et al, 2016 ; Bowden et al, 2018 ; Chow et al, 2016 ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In regard to resting-state fMRI, our results suggest that both neuronal desynchronization and neurovascular disruption could contribute to apparent changes in fMRI-based measures of “functional connectivity” related to tumor progression ( Dierker et al, 2017 ; Hadjiabadi et al, 2018 ). Nevertheless, these results do suggest a firm physiological basis for studies that have noted the ability of resting state fMRI data to delineate glioma tumor boundaries ( Agarwal et al, 2016 ; Bowden et al, 2018 ; Chow et al, 2016 ).…”
Section: Discussionmentioning
confidence: 73%
“…Tumor-dependent alterations in neurovascular coupling could lead to misinterpretation of fMRI data, and errors in the localization of functional boundaries. Several recent human resting-state fMRI studies have also shown that gliomas can cause focal changes in the BOLD signals detected in the tumor and surrounding infiltrated cortex, characterized by a loss of synchrony between the tumor and the contralateral hemisphere ( Agarwal et al, 2016 ; Bowden et al, 2018 ; Chow et al, 2016 ). Although these studies could not disambiguate whether changes in BOLD were caused by altered neuronal activity, neurovascular coupling, or both, they suggest that vascular signals could be helpful biomarkers of tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…The slides were then scanned and digitized at 40x magnification on a Leica SCN400 system (Leica Biosystems). Total cell density and SOX2 + nuclei were measured using a semi-automated cell-counting algorithm as previously described (49). Algorithm-derived cell counts were manually verified, and total cell density and SOX2 cell density were assessed for one representative high-power field from each sample.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…In regards to resting-state fMRI, our results suggest that both neuronal desynchronization and neurovascular disruption could contribute to apparent changes in fMRI-based measures of 'functional connectivity' related to tumor progression (Hadjiabadi et al, 2018) (Dierker et al, 2017). Nevertheless, these results do suggest a firm physiological basis for studies which have noted the ability of resting state fMRI data to delineate glioma tumor boundaries (Bowden et al, 2018) (Chow et al, 2016) (Agarwal et al, 2016).…”
Section: Progressive Disruption Of Neurovascular Couplingmentioning
confidence: 66%
“…Tumor-dependent alterations in neurovascular coupling could lead to misinterpretation of fMRI data, and errors in the localization of functional boundaries. Several recent human resting-state fMRI studies have also shown that gliomas can cause focal changes in the blood oxygen level dependent (BOLD) signals in the tumor and surrounding infiltrated cortex, characterized by a loss of synchrony between the tumor and the contralateral hemisphere (Bowden et al, 2018) (Chow et al, 2016) (Agarwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%